The politics of property rights institutions in Africa - Onoma, Ato Kwamena, 1975- (Cambridge ; New York : Cambridge University Press, 2010)
"Why do some political leaders create and strengthen institutions su ch as title registries and land tribunals that secure property rights t o land, while others neglect these institutions or destroy those that a lready exist? How do these institutions evolve once they have been esta blished? This book answers these questions through spatial and temporal comparison of national and subnational cases from Botswana, Ghana, and Kenya, and, to a lesser extent, Zimbabwe. Onoma argues that the level of property rights security that leaders prefer depends on how they use land. However, the extent to which leaders' institutional preferences are translated into actual institutions depends on the level of leaders ' capacity. Further, once established, these institutions through their very working can contribute to their own decline over time. This book is unique in revealing the political and economic reasons why some lead ers, unlike others, prefer an environment of insecure rights even as la nd prices increase"--Provided by publisher.
Divergent attitudes towards property rights institutions -- Explaini ng institutional choice and change -- Varying responses by Ghanian and Batswanaian state leaders -- Traditional leaders take charge in Akyem A buakwa and Ga -- Building and then demolishing institutions in Kenya -- Endogenous contributions to institutional change.
Includes bibliographical references and index.
Keywords: Right of property